(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
One of the most effective educational tools for developing language learners' critical and analytical thinking abilities is questioning. Effective questioning techniques can develop students' critical thinking, information analysis, and effective communication skills by stimulating curiosity, increasing introspection, and fostering deep engagement with the course material. This article examines the value of questioning in language classes and offers suggestions for purposeful questioning strategies that can strengthen students' capacity for critical and analytical thought.